tykearasmith
tykearasmith
15-07-2015
Mathematics
contestada
Solve the equation.
−10x + 1 + 7x = 37
Respuesta :
ivanzud
ivanzud
15-07-2015
You combine like terms which are -10x and 7x and 1 and 37. Then it becomes -3x=36. x would equal to 36/-3, which is -12.
Answer Link
Аноним
Аноним
15-07-2015
−10x+1+7x=37
Simplify both sides of the equation.
−10x+1+7x=37
Simplify:
−10x+1+7x=37
(−10x+7x)+(1)=37(Combine Like Terms)
−3x+1=37
−3x+1=37
Subtract 1 from both sides.
−3x+1−1=37−1
−3x=36
Divide both sides by -3.
−3x/−3 = 36/−3
x=−12
Answer Link
VER TODAS LAS RESPUESTAS ( 59+ )
Otras preguntas
how do you write a multiplication equation with 1/2 as a factor
In Ancient Greece, Euclid contributed to a better understanding of
If transpiration stopped completely, how would a plant's homeostasis first be affected?
The blackberry's seeds must be digested by a bird before they can sprout. What type of relationship do the blackberry plants and the birds have? A. commensali
Why was the Warren Commission created in November 1963?
¿Cómo vas al supermercado de tu casa?
Compare and contrast how Sara and little willy react to the challenges they face
What causes the lunar phases that we see from earth
a bag contains green Marbles and purple marbles if a marble is randomly selected from the bag the probability that it is green is 0.6 and the probability that i
write the closest benchmark for the percent for 48%